The Implications of Accounting Distortions and Growth for Accruals and Profitability - Richardson, Scott A.; Sloan, Richard G.; Soliman, Mark T.; Tuna, I˙rem (The Accounting Review, 2006)
Following Sloan (1996), numerous studies document that the accrual component of earnings is less persistent than the cash flow component of earnings. Disagreement exists, however, as to the explanation for this result. One stream of literature follows Sloan's lead in arguing that this result is attributable to accounting distortions (Xie 2001; Dechow and Dichev 2002; Richardson et al. 2005). A second stream of literature argues that this result is attributable to a more general growth effect and that growth-related factors such as diminishing returns to new investment explain the lower persistence of accruals (e.g., Fairfield et al. 2003a; Cooper et al. 2005). We provide new evidence indicating that temporary accounting distortions are a significant contributing factor to the lower persistence of the accrual component of earnings. Our evidence indicates that the lower persistence of accruals extends to accruals that are unrelated to sales growth and that extreme accruals are systematically associated with alleged cases of earnings manipulation.